Changes in cortical auditory evoked potentials in response to auditory training in elderly hearing aid users: A pilot study - Alcântara, Yara Bagali [UNESP]; Toledo, Willians Walace Fante [UNESP]; de Lima, Karoline Ribeiro [UNESP]; Carnaúba, Aline Tenório Lins; Chagas, Eduardo Federighi Baisi; Frizzo, Ana Claudia Figueiredo [UNESP] (Public Library of Science (PLoS), 2022)
Objective To compare the cortical auditory evoked potential responses pre-and post-Auditory Musical Training associated with hearing aid adaptation in elderly people with presbycusis. Design This is a pilot, prospective, randomized, single-blind study. Study sample Eight presbiacusis elderly people between 65 and 80 years, new hearing aid users, divided into two groups participated in the study: Hearing Aid Group: use of hearing aid; and Auditory Training Group: use of hearing aid in addition to musical auditory training for 16 sessions. All participants were submitted to cortical auditory evoked potential tests with verbal stimulation in two different moments: Initial assessment, carried out before hearing aid adaptation and auditory training, and after three months, final assessment at the end of the auditory training sessions. All participants were adapted bilaterally with digital mini hearing aids. Results There was a decrease in the P3a latency component for the Auditory Training Group when initial and final assessment were compared. Conclusion There was a change in the cortical auditory evoked potential in elderly people with presbycusis in response to the Musical Auditory Training associated with the use of hearing aids in elderly people with presbycusis.